Characterization of Activated Charcoal Oil Palm (Elaeis Guineensiss Jacq) Shell Waste using SEM and FTIR: Effect of Activation Temperature - Rasyid Syidiq; La Ode Yusran; Muhammad Anas; Suritno Fayanto (Universitas Ahmad Dahlan, 2022)
This study aims to determine the structure of morphology and functional groups from activated charcoal for palm oil waste with variations in activation temperature. The process of two stages: the carbonation and activation stage. Carbonation process using a pyrolysis reactor at a carbonation temperature of 200oC -400oC for 6 hours. Then, the sample activated at a temperature of 700 °C, 750oC, 800oC, and 850 °C. Samples were characterization using SEM and FTIR. SEM analysis results show the largest pore size at a temperature of 850 oC with a diameter of 48.3 nm, and the lowest temperature was 700 °C with a capacity of 35.3 nm. Activated charcoal from oil palm shell waste at mesopore size. Next, FTIR analysis results show wave numbers 2165,18 cm-1, 1554 cm-1, 1030,76 cm-1 dan 424,11 cm-1. The removal of some absorption bands and the formation of new absorption bands, caused by the activation temperature